Upconversion nanoparticles for bioimaging - Song Chenxi; Zhang Shubiao; Zhou Quan; Hai Hua; Zhao Defeng; Hui Yunze (Nanotechnology Reviews, 2017)
Fluorescent labeling is a widely used indispensable tool in biology. Conventional downconversion fluorescence labels with ultraviolet or short-wavelength excitation suffer from autofluorescence, low signal-to-noise ratio, and incident photo damage to living organisms. However, upconverting fluorescent nanoparticles emit detectable photons of higher energy in the near-infrared (NIR) or visible range upon irradiation with a NIR light in a process termed upconversion. They overcome some of the disadvantages faced by conventional downconversion labels with the advantages including very low autofluorescence, absence of photo damage to living organisms, high detection sensitivity, and high depth of light penetration, thus making them an ideal fluorescent label for bioimaging. The present review focuses on the features of upconversion nanoparticles, the applications of upconversion nanoparticles in bioimaging, and the bioimaging equipments and methods and discusses the obstacles and development trend of upconversion nanoparticles in bioimaging; we hope this work will provide insights into the study of relevant fields. Upconversion nanoparticles have special photoluminescent properties. Substantial advancements have been made in the field of upconversion nanoparticles for bioimaging. A large number of modifications of upconversion nanoparticles are studied to make them more hydrophilic and biocompatible. At the same time, the safety and toxicity of nanoparticles have caused wide public concern.